Heavy metal bioremediation of coal-fired flue gas using microalgae under different CO2 concentrations. (1st July 2019) - Aslam, Ambreen; Thomas-Hall, Skye R.; Mughal, Tahira; Zaman, Qamar-uz; Ehsan, Nusrat; Javied, Sabiha; Schenk, Peer M.
Abstract: Sustainability assessments have revealed that integration of CO2 from coal-fired flue gas with microalgae cultivation systems could reduce greenhouse gas emissions. The technical goal of this integration is to utilize exhaust from coal power plants to enhance microalgae cultivation processes by capturing and recycling of carbon dioxide from a more toxic to a less toxic form. However, heavy metals are also introduced along with CO2 to the cultivation system which could contaminate biomass and have deleterious effects on products derived from such systems. The present study aimed at shedding some light on capability of microalgae to sustain their diversity and propagate them under different CO2 concentrations from coal-fired flue gas. Mixed microalgal culture was grown in nutrient rich medium and heavy metals (Al, Cu, Fe, Mn and Zn) are expected to be introduced from flue gas. Three concentrations (1%, 3% and 5.5%) of CO2 were evaluated (reference concentrations from flue gas). Comparative studies were carried out by flue gas and control systems in photobioreactors. Under the 3% CO2 (30% flue gas), the highest fraction of B, Mn and Zn were found to be internalized by the cells (46.8 ±9.45 gL-1, 253.66 ± 40.62 gL-1 and 355.5 ±50.69 gL-1 respectively) during their cultivation period into biomass. Hence, microalgae may offer solution to two major challenges: providing potential biofuel feedstock for energy security and reducing heavy metal pollution to the air. Highlights: Heavy metal bioremediation under three CO2 (flue gas) concentrations. Outdoor photobioreactor was used for mixed microalgae cultivation. Photobioreactors connected with unfiltered smoke stack of a 4 MW coal-fired boiler. Comparative studies conducted in batch cultivation of flue gas (CO2 ) and control systems. Highest fraction of metals were internalized at 3% CO2 (flue gas) concentration.